Structural analysis of a soluble polysaccharide GSPA-0.3 from the root of Panax ginseng C. A. Meyer and its adjuvant activity with mechanism investigation - Feng, Lei; Han, Na; Han, Yu-Bo; Shang, Meng-Wen; Liang, Teng-Wei; Liu, Zhi-Hui; Li, Si-Kai; Zhai, Jian-Xiu; Yin, Jun (Carbohydrate polymers, 2024)
A novel polysaccharide (GSPA-0.3) was isolated and purified from the root of cultivated Panax ginseng C. A. Meyer, and its structure, adjuvant activities, and mechanisms for inducing the maturation of mouse dendritic 2.4 cells (DC2.4) were extensively studied. Fraction GSPA-0.3, mainly composed by the galacturonic acid, galactose, arabinose, glucose, rhamnose, mannose, and xylose, had a molecular weight of 62,722 Da. The main chain of GSPA-0.3 was composed of →3)-α-L-Rhap-(1→, →4)-α-D-GalpA-(1→, and →3, 4)-α-D-GalpA-(1→. Branched chains comprised α-L-Araf-(1→3, 5)-α-L-Araf-(1→5)-α-L-Araf-(1→, α-D-Glcp-(1→6)-α-D-Glcp-(1→6)-α-D-Glcp-(1→, β-D-Galp-(1→4)-β-D-Galp-(1→4)-β-D-Galp-(1→, and α-D-GalpA-(1→ units connected to the C3 position of →3, 4)-α-D-GalpA-(1→. In vivo, GSPA-0.3 was found to stimulate the production of IgG, IgG1, and IgG2a; increase the splenocyte proliferation index; and promote the expression of GATA-3, T-bet, IFN-γ, and IL-4 in H1N1 vaccine-immunized mice. Moreover, GSPA-0.3 significantly increased the levels of neutralizing antibodies in the mice, and its adjuvant activity was found to be superior to aluminum adjuvant (Alum adjuvant). Mechanistic investigations showed that GSPA-0.3 activated the TLR4-dependent pathway by upregulating the expressions of TLR4, MyD88, TRAF-6, and NF-κB proteins and gens. The results presented herein suggested that GSPA-0.3 could significantly promote the efficacy of the H1N1 vaccine by modulating Th1/Th2 response via the TLR4-MyD88-NF-κB signaling pathway.